2013
DOI: 10.1101/gr.154625.113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variable retroduplications in human populations suggests coupling of retrotransposition to cell division

Abstract: In primates and other animals, reverse transcription of mRNA followed by genomic integration creates retroduplications. Expressed retroduplications are either “retrogenes” coding for functioning proteins, or expressed “processed pseudogenes,” which can function as noncoding RNAs. To date, little is known about the variation in retroduplications in terms of their presence or absence across individuals in the human population. We have developed new methodologies that allow us to identify “novel” retroduplication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 70 publications
(89 reference statements)
2
54
0
2
Order By: Relevance
“…Besides the retroduplication calls shared among callsets, there are also large number of calls unique to our callset, which is likely due to newly enrolled populations in Phase 3 data, and the higher sensitivity of our methods. We resolved 152/503 (30.2%) insertion sites for our predicted retroduplications, a percentage higher than previous studies [5,7]. Functional enrichment analysis for the 503 unique parent genes shows the most enriched functions are related to ribosome/structural molecule activity, intracellular organelle lumen/nucleoplasm, and protein complex assembly.…”
Section: Resultsmentioning
confidence: 72%
“…Besides the retroduplication calls shared among callsets, there are also large number of calls unique to our callset, which is likely due to newly enrolled populations in Phase 3 data, and the higher sensitivity of our methods. We resolved 152/503 (30.2%) insertion sites for our predicted retroduplications, a percentage higher than previous studies [5,7]. Functional enrichment analysis for the 503 unique parent genes shows the most enriched functions are related to ribosome/structural molecule activity, intracellular organelle lumen/nucleoplasm, and protein complex assembly.…”
Section: Resultsmentioning
confidence: 72%
“…Furthermore, LINE-1-mobilized sequences in cultured cells (Berry et al 2006), tumors Tubio et al 2014), and mice bearing an engineered LINE-1 element are not preferentially targeted to piRNA clusters. Finally, recent processed pseudogene (Abyzov et al 2013) and retrotransposon insertions in human genomes are not enriched within piRNAgenerating loci (Y Zhang and P Gerstein, pers. comm.).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have also shown that retrotransposition likely occurs during cell division given that many retroCNV cognate genes are expressed during this phase of the cell cycle (Abyzov et al 2013). Importantly, the recent origin of most retroCNVs has led to the identification of molecular signatures specific of either LINEs or LTR retroelements in plants and animals, expanding on the limited perspective offered by studies in mammals wherein L1 elements have been primarily involved in the formation of retrocopies.…”
Section: Evolutionary Insights From Retrocnvsmentioning
confidence: 99%
“…Additionally, retroCNVs appear to form at a lower rate than CNVs generated through DNA duplication in humans (Abyzov et al 2013). …”
Section: Distribution Of Retropseudogenes and Retrogenes In Eukaryotesmentioning
confidence: 99%